Authority, politicization, and alternative justifications: endogenous legitimation dynamics in global economic governance - Christian Rauh; Michael Zürn (Review of International Political Economy, 2020)
Recent mobilization against core tenets of the liberal international order suggests that international institutions lack sufficient societal legitimacy. We argue that these contestations are part of a legitimation dynamic that is endogenous to the political authority of international institutions. We specify a mechanism in which international authority increases the likelihood for the public politicization of international institutions. This undermines legitimacy in the short run, but also allows broadening the justificatory basis of global governance: Politicization allows civil society organizations (CSOs) to transmit alternative legitimation standards to global elite discourses. We trace this sequence for four key institutions of global economic governance – the IMF, the World Bank, the WTO, and the NAFTA – combining data on authority and protest counts with markers for CSOs and legitimation narratives in more than 120,000 articles in international elite newspapers during 1992–2012. The uncovered patterns are consistent with a perspective that understands legitimation dynamics as an endogenous feature of international authority, but they also show that alternative legitimation narratives did not lastingly resonate in the global discourse thus far. This may explain current backlashes and calls for active re-legitimation efforts on part of international institutions themselves.
doi:10.7910/DVN/FZ1HZR
Keywords: 330; legitimacy; legitimation; IMF; World Bank; WTO; NAFTA; politicization